Formation Of A Moral Ideal Through The Image Of An Athlete - Sultanov Bakhtiyor Bakhtiyorovich (Periodica Journal, 2025)
This article is devoted to the study of the role of the athlete’s image in shaping the moral ideal of an individual. The athlete, as a social symbol, embodies such qualities as discipline, determination, honesty, perseverance, and respect for opponents, which make this image a powerful tool for fostering moral values. Through the analysis of sports activities, biographies of outstanding athletes, and their influence on society, the article examines how these qualities can serve as moral examples, promoting the development of ethical principles, responsibility, and the pursuit of self-improvement among youth and society as a whole. The study also explores key concepts such as “glory,” “calling,” “service,” and “mission” within the context of sports, viewing them as essential components contributing to success.
Keywords: Ideal; moral ideal; calling; image